When we look at the supervisor image in the mirror, what do we see? The supervisors’ mirror image regarding doctoral supervision - Coutinho, Isabel Ribau (Advances in Social Sciences Research Journal, 2021)
Studies regarding doctoral education can focus the PhD student, the supervisor, higher education institution (policy, curriculum, professional career support, culture, among others). PhD students, supervisors and higher education institution, constitute three keys for the same door (doctoral education), and without one of them, the door can´t be well open. Choose which of them should be analyzed is the researcher responsibility, as present data and look carefully to it. During the last years’ doctoral education and the doctoral supervision process at UNL as been studied, looking to PhD students, supervisors and institution [1-5]. In the present research, the focus is on supervisor perception. It is important to know supervisor opinion, to attempt and captures their perceptions regarding the doctoral supervision process. When the supervisor thinks and responds to surveys regarding supervision, he/she is presenting an image of himself/herself. This study occurred among the PhD supervisor population at a Science engineering school (Faculdade de Ciências Tecnologia) at Universidade Nova de Lisboa, a Portuguese Higher education institution, with a footprint in the research area. It was possible to capture the image that reflected in the mirror when the supervisor looked. The unexpected image reflected is of a researcher and not a supervisor. When they look to their doctorates, they generally see future technicians/ qualified workers and not a future researcher. Nonetheless, they consider that to finish the PhD, doctorates have to acquire the research profile. This mismatch is consistent with the reality, where attrition exists and many students think to live the academy after the enrollment in the PhD.